If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + 11 = -73 + -9x Reorder the terms: 11 + 5x = -73 + -9x Solving 11 + 5x = -73 + -9x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '9x' to each side of the equation. 11 + 5x + 9x = -73 + -9x + 9x Combine like terms: 5x + 9x = 14x 11 + 14x = -73 + -9x + 9x Combine like terms: -9x + 9x = 0 11 + 14x = -73 + 0 11 + 14x = -73 Add '-11' to each side of the equation. 11 + -11 + 14x = -73 + -11 Combine like terms: 11 + -11 = 0 0 + 14x = -73 + -11 14x = -73 + -11 Combine like terms: -73 + -11 = -84 14x = -84 Divide each side by '14'. x = -6 Simplifying x = -6
| 3d+5d+2= | | 10s-4=8 | | -104=8(r-8) | | .3-1.6=.625m | | -6d-6=12 | | 2(x+3)=10(2+4x) | | 17=z/3-21 | | (x-5)(2x+3)-2x(x+1)=0 | | 3x-5=4x+5-x | | -4(3k-8)=128 | | 3-4+11=2 | | 4n+20=2n-4 | | x-(-19)=23 | | 5y-5x=10 | | -15+5y=25 | | -(n-8)=-4+2(n-6) | | 3v+5=3v+5 | | 24=6+2(3x) | | 36c^9+12=0 | | 36c^9+12=0 | | 8x-48=6x+22 | | 8y+6-2y=18 | | x(6x-11)=3 | | 7x-3=4x-27 | | -2x+5y=12findy | | 16p^6-5p^4-10p^2=0 | | -a-2+8=2a-12 | | 2.094x=30 | | 6x+6+2x=2x-4-4x | | [b]=2/3 | | 407=35+x+(40-x)2 | | 32X^4-4x=0 |